(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to evaluate the correlation between body mass index (BMI) and hematological parameters in students of the medical laboratory techniques at Nguyen Tat Thanh University. Methods: A cross-sectional study was conducted on 185 students enrolled in the Medical Laboratory Techniques at Nguyen Tat Thanh University. Results: The rate of underweight students is 22.2%, with female students accounting for a higher proportion (17.3%). Conversely, the prevalence of overweight and obesity tended to be higher among male students, with rates of 9.2% and 7%, respectively. Hematological indices in the red blood cell line tended to be higher in males, while white blood cell indices tended to be higher in females. Furthermore, hematological indices showed an increasing trend from the underweight group to the overweight/obese groups. This association was statistically significant for RBC (r = 0.32, p < 0.01) and HGB (r = 0.27, p < 0.01). Conclusion: This study found that the majority of students possess BMI indices within the normal range, yet there remains a significant proportion of students who are overweight, obese, or underweight. A clear correlation exists between BMI and several hematological parameters, specifically RBC, HGB, Hct, WBC. Students in the overweight,obese group tend to show elevated levels of these indices, while the underweight group exhibits decreased levels. The findings emphasize the importance of maintaining a proper BMI level to safeguard hematological health and prevent nutrition-related blood disorders.